2015
DOI: 10.18097/pbmc20156106742
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of taxonomic and functional changes in gut microbiota of patients with alcoholic dependence syndrome

Abstract: ВВЕДЕНИЕБольшинство исследований синдрома алкогольной зависимости (САЗ) посвящено его нейрофизиологическим [1] последствиям и влиянию на функционирование печени и других органов человека, тогда как вопрос воздействия потребления алкоголя на микрофлору кишечника человека остаётся малоизученным [2]. Поскольку диета является одним из основных факторов, оказывающих влияние на видовой состав и функциональную активность микробиоты, можно предположить, что алкоголь и продукты его деградации будут существенно модулиро… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In humans, lower levels of A. muciniphila have also been found in patients with inflammatory digestive diseases and ALDs, especially those induced by an excessive ethanol consumption, whether in the gut [ 110,111 ] or in the blood of patients with cirrhosis. [ 112 ] Lang et al [ 113 ] also demonstrated higher changes in the gut bacterial microbiome of patients with hepatitis due to ALD, proportional to the severity of the disease that were correlated with a significant decrease of A. muciniphila .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, lower levels of A. muciniphila have also been found in patients with inflammatory digestive diseases and ALDs, especially those induced by an excessive ethanol consumption, whether in the gut [ 110,111 ] or in the blood of patients with cirrhosis. [ 112 ] Lang et al [ 113 ] also demonstrated higher changes in the gut bacterial microbiome of patients with hepatitis due to ALD, proportional to the severity of the disease that were correlated with a significant decrease of A. muciniphila .…”
Section: Resultsmentioning
confidence: 99%
“…[105] The authors suggested that Akkermansia was able to regulate immune system functions through the production of short-chain fatty acids (SCFAs) by metabolizing the complex glycans as a carbon source such as those provided by the mucus layer like N-acetylglucosamine and Nacetylgalactosamine [20,106] or arabinoxylans and inulin, [107][108][109] reducing then the systemic inflammation. [105] In humans, lower levels of A. muciniphila have also been found in patients with inflammatory digestive diseases and ALDs, especially those induced by an excessive ethanol consumption, whether in the gut [110,111] or in the blood of patients with cirrhosis. [112] Lang et al [113] also demonstrated higher changes in the gut bacterial microbiome of patients with hepatitis due to ALD, proportional to the severity of the disease that were correlated with a significant decrease of A. muciniphila.…”
Section: Influence Of Ethanol On a Muciniphilamentioning
confidence: 99%
“…properties (Bjorkhaug et al, 2019;Jiao et al, 2022). AUD patients showed a consistent proinflammatory profile (Dubinkina et al, 2015).…”
Section: Exploring the Gut Microbiome In Alcohol Use Disorder Excludi...mentioning
confidence: 92%
“…Human and/or experimental research demonstrates that the risk of microbial dysbiosis is increased by acute and cumulative psychological and physical (e.g., thermal, noise) stress [275,276,277,278,279,280,281], environmental pollutants including lead, polycyclic aromatic hydrocarbons and airborne particulate matter [282,283,284], tobacco exposure [285,286,287] and excess alcohol consumption [288]. In addition, the oral periodontopathogen P. gingivalis , reported to be much higher in North American disadvantaged populations [289] has recently been shown to cause dysbiosis when swallowed [290].…”
Section: Hygiene Hypothesis Dysbiotic Driftmentioning
confidence: 99%